2009
DOI: 10.1158/1535-7163.mct-09-0499
|View full text |Cite
|
Sign up to set email alerts
|

BMS-754807, a small molecule inhibitor of insulin-like growth factor-1R/IR

Abstract: BMS-754807 is a potent and reversible inhibitor of the insulin-like growth factor 1 receptor/insulin receptor family kinases (Ki, <2 nmol/L). It is currently in phase I development for the treatment of a variety of human cancers. BMS-754807 effectively inhibits the growth of a broad range of human tumor types in vitro, including mesenchymal (Ewing's, rhabdomyosarcoma, neuroblastoma, and liposarcoma), epithelial (breast, lung, pancreatic, colon, gastric), and hematopoietic (multiple myeloma and leukemia) tumor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
222
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(236 citation statements)
references
References 41 publications
10
222
2
2
Order By: Relevance
“…In our studies, there was no apparent in vivo toxicity during a 2-week treatment course, however, toxicity for long-term inhibition of the IGF-1R and IR functions remains to be elucidated. A previous study reported only a short-term increase in serum glucose or insulin levels at doses up to 12.5 mg/kg, with an average weight change of −1.5 grams at 25 mg/kg, but no mortality [33]. In our study, no significant change in mouse body weight was observed by BMS-754807 therapy, but blood glucose measurements were not obtained.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…In our studies, there was no apparent in vivo toxicity during a 2-week treatment course, however, toxicity for long-term inhibition of the IGF-1R and IR functions remains to be elucidated. A previous study reported only a short-term increase in serum glucose or insulin levels at doses up to 12.5 mg/kg, with an average weight change of −1.5 grams at 25 mg/kg, but no mortality [33]. In our study, no significant change in mouse body weight was observed by BMS-754807 therapy, but blood glucose measurements were not obtained.…”
Section: Discussioncontrasting
confidence: 60%
“…The IGF signaling inhibitor BMS-754807 has shown antitumor activity in multiple tumor models including epithelial, mesenchymal and hematopoietic cancer cells [33]. We observed the effect of BMS-754807 in subcutaneous xenografts using two aggressive PDAC cell lines, AsPC-1 and Panc-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 48 h, the pAkt signal was observed in clustered and likely newly divided cells (Figure 3c, see insert). To test whether this Ca 2 þ deficiency-induced Akt activation is downstream of the IGF1R, two structurally distinct IGF1R inhibitors, BMS-754807 19 and NVP-AEW541 20 were used. Blockage of the IGF1R-mediated signaling abolished pAkt signal under low [Ca 2 þ ] (Figures 3d and e).…”
Section: Resultsmentioning
confidence: 99%
“…Recombinant enzymes were purchased from Invitrogen (Carlsbad, CA, USA) or produced as described previously. 24 Keyhole limpet hemocyanin (KLH) used for immunization was purchased from Pierce (Rockford, IL, USA). SET2 cells were obtained from DSMZ (Braunschweig, Germany).…”
Section: Reagentsmentioning
confidence: 99%